2023
DOI: 10.21203/rs.3.rs-2524702/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined β-Sitosterol and Trimetazidine mitigate potassium dichromate-induced cardiotoxicity in rats through the interplay between NF-κB/AMPK/mTOR/TLR4 and HO-1/NADPH signaling pathways

Abstract: Hexavalent chromium salt, like potassium dichromate (PD), is chromium's most precarious valence state, present in industrial wastes. Recently, there has been increasing interest in β-sitosterol (BSS), a bioactive phytosterol, as a dietary supplement. BSS is recommended in treating cardiovascular disorders due to its antioxidant effect. Trimetazidine (TMZ) was used traditiovally for cardioprotection. Through the administration of BSS and TMZ, the cardiotoxic effects of PD were to be countered in this study, in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…The present results highlight the pronounced effects of nicorandil on AMPK phosphorylation in ATO‐treated rats. This aligns with other studies demonstrating the protective antioxidant role of AMPK, which suppresses NF‐κB activity and impedes its migration from the cytosol of activated macrophages to the nucleus, thereby restraining the initiation of the pro‐inflammatory cascade (El‐Shoura et al, 2023; Xiang et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results highlight the pronounced effects of nicorandil on AMPK phosphorylation in ATO‐treated rats. This aligns with other studies demonstrating the protective antioxidant role of AMPK, which suppresses NF‐κB activity and impedes its migration from the cytosol of activated macrophages to the nucleus, thereby restraining the initiation of the pro‐inflammatory cascade (El‐Shoura et al, 2023; Xiang et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, disturbed redox balance and heightened levels of oxidative stress biomarkers are known to trigger NF‐κB activation via TLR‐4. This activation exacerbates the redox status imbalance, stimulating an increased influx of inflammatory cells and cytokines, including TNF‐α, IL‐6, and IL‐1β, while concurrently decreasing levels of anti‐inflammatory cytokines (Atwa et al, 2022; Baeuerle & Baichwal, 1997; El‐Shoura et al, 2023). Cytokine activation stimulates STATs through JAK activation via tyrosine phosphorylation (Liu et al, 2023; Morris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These effects were associated with modulation of PPARγ/NF-κB signaling during myocardial I/R El Omari et al Natural Products and Bioprospecting (2024) 14:27 injury. Recently, El-Shoura et al [149] investigated the effectiveness of a combination therapy of β-sitosterol with trimetazidine (TMZ) to attenuate experimentally induced cardiotoxicity (in vivo). Study results showed that the administration of β-sitosterol alone or combined with TMZ provides high protection against cardiotoxicity by decreasing oxidative stress as well as inflammatory and apoptotic biomarkers.…”
Section: Other Protective Mechanismsmentioning
confidence: 99%